Prognostic value of auditory brainstem response for neurologic outcome in patients with neonatal indirect hyperbilirubinemia - ÇİPRUT, AYŞE AYÇA (B C DECKER INC, 2001)
To investigate the value of the auditory brainstem response as a reliable test for the neurologic prognosis. of infants. with neonatal indirect hyperbilirubinemia, auditory brainstem response studies were performed in 22 infants. The patients were followed up until 12 months of age. Two patients demonstrated pathologic auditory brainstem response consistent with auditory neuropathy but had no neurologic finding except a lack of speech at 12 months of age. Two other patients had neurologic sequelae, one showing severe dyskinetic cerebral palsy, the other mild hypotonia and motor retardation, but their auditory brainstem response results were normal. These results suggested that auditory brainstem response examination might not provide reliable information for the neurologic prognosis. Neurologic disturbances resulting from bilirubin neurotoxicity can be seen in patients with a normal auditory brainstem response, but patients with an abnormal auditory brainstem response may not have any neurologic dysfunction apart from speech retardation.
Keywords: STEM RESPONSES; EXCHANGE-TRANSFUSION; EVOKED-POTENTIALS; FOLLOW-UP; FULL-TERM; BILIRUBIN; INFANTS; KERNICTERUS; NEWBORN; NERVE